Meet Josefina : an American girl - Tripp, Valerie, 1951-; Tibbles, Jean-Paul; McAliley, Susan (Middleton, WI : Pleasant, 2000)
Nine-year-old Josefina, the youngest of four sisters living in New Mexico in 1824, tries to help run the household after her mother dies.
"American girl."
"Book 1"--Cover.
3.5
3-6
Keywords: Ranch life -- New Mexico -- Fiction; Mexican Americans -- Fiction; Sisters -- Fiction; Aunts -- Fiction; New Mexico -- History -- To 1848 -- Fiction; Historical fiction; Ranch life -- Fiction; Mexican Americans -- Fiction; Sisters -- Fiction; Aunts -- Fiction; New Mexico -- History -- Fiction; Historical fiction